The Influence Of Strategic Orientation Dimensions On Market Performance During Covid-19 Pandemic: A Study Of Culinary Business In Kendari City, Indonesia - Hapsari, Indri; Lampasa, Yunitawati; Marjani, Marjani; Juwita, Juwita; Bugis, Hairudin (Jurnal Manajemen Industri dan Logistik, 2022)
This study aimed  to analyze the effect of the strategic orientation dimension on the  culinary business market performance  in Kendari City during the Corona Virus Disease Pandemic. The method used was descriptive quantitative with a non-probability sampling approach with purposive sampling technique. The population was culinary business actors who still survive and have been running for the business more than 2 years during the COVID-19 pandemic. The  sample in this study only obtained 38 respondents. The data analysis technique in this research was  path analysis using SmartPLS VS 3.0. The results showed  an analysis of the strategic dimensions that have an aggressive attitude and had  significant effect on market performance so that culinary business actors can improve their market performance during the COVID-19 pandemic.